Two new species of Atanatolica Mosely 1936 (Trichoptera: Leptoceridae) from Peru and Northeastern Brazil - Henriques-Oliveira, A. L.; Santos, A. P.m. (Zootaxa, 2014)
We describe and illustrate two new species of Atanatolica from Brazil and Peru, representing the first record of the genus from Peru and the first record of the genus from Ceará state, Brazil. Atanatolica nordestina sp. nov. is recognized by short inferior appendages, with their basal portions subquadrangular, in ventral view; and by tergum X without the typical digitate apical processes, but with a pair of short rounded projections. Atanatolica quechua sp. nov. is recognized by preanal appendages long and slender, by the inferior appendages with the apicodorsal portion broader distally, and by the apicolateral processes of tergum X slightly capitate.